How Trust Empowers Motivation and Knowledge Sharing to Improve Performance: A Moderated Mediation Model - Iwan Sidharta (Acman: Accounting and Management Journal, 2026)
This study investigates the structural relationships among trust, motivation, knowledge sharing, and employee performance in the retail sector. Specifically, we examine how motivation and knowledge sharing mediate the impact of trust, while evaluating the conditional boundaries and essential prerequisites of these relationships. Author adopted a quantitative approach, surveying 154 retail employees. The data analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the structural model, supplemented by Importance-Performance Map Analysis (IPMA) and Necessary Condition Analysis (NCA) to identify performance priorities and operational bottlenecks. The structural analysis reveals that trust exerts a powerful medium effect on knowledge sharing, which subsequently drives employee performance. Furthermore, NCA establishes trust as a critical, mandatory bottleneck (Strong Necessity) for maximizing performance, while motivation and knowledge sharing act as Moderate Necessity conditions that restrict peak outcomes if neglected. Retail managers must actively build organizational trust to dismantle information silos and unlock the positive benefits of employee motivation. To achieve superior performance targets, management should prioritize resources toward knowledge sharing during briefings and establish clear incentive structures to maintain high motivational ceilings. This study offers unique value by integrating PLS-SEM with advanced IPMA and NCA methodologies in a retail context. Rather than just examining linear relationships, this research uncovers the exact necessary thresholds and bottleneck values of trust and motivation required to achieve optimal employee productivity.